Hermeneutic practices in software development: the case of Ada and Python. - Binzberger, Viktor (Techné: Research in Philosophy & Technology)
This paper shows the relevance of hermeneutic philosophy to understand how info-communication technologies frame our contemporary lifeworld. It demonstrates that the programming languages are the result of collective interpretations of the general lifeworld of programmers, management and political decision-makers. By having been inscribed into the processes of language use, this general interpretation permeates the particular practices of understanding that are possible within the language framework. I support my argument by contrasting the hermeneutic concerns about the understanding between programmers which stand behind the design of the Ada and the Python programming languages. Ada, with its emphasis on achieving seamless communication through rationalistic standardization and the technical embodiment of the background of understanding, bears the imprint of the culture of Cold War-era DoD-funded military projects. On the other side, Python is inscribed with a culture of open-ended discussion and self-reflective practices of conventionalization that is characteristic of the FLOSS world.